Methods of foreign language formation of professionally-oriented students communicative competence in a technical university (on the basis of the english language) - Elena A. Mitrofanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author examines the training manual created by the department of SSTU to prepare students, bachelors, masters of the Oil- Technological Department, Department of Engineering, Metallurgy and Transport and Department of Automation and Information Technology. The purpose of these text books is the formation of foreign language professionally-oriented competence of students. The structure of text books, types of lexical and grammatical tasks and techniques of teaching reading and text abstracting are considered.